Aplikasi Penanda Lima Primer RAPD (Random Amplified Polimorphic DNA) untuk Analisis Keragaman Genetik Andaliman (Zanthoxylum acanthopodium DC) Sumatera Utara - indriani maya sari sembiring (Universitas Sumatera Utara, 2016)
The aim of the research was to determine the genetic diversity of the North Sumatera andaliman plants based on the RAPD using the OPD-13, OPI-20, OPH-09, OPN-10, OPM-01 primers. The research was conducted at the Integrated Laboratory, Faculty of Medicines, North Sumatera University from April 2015 to September 2015. Thirty accessions of North Sumatera andaliman plants were observed which originated from three districts i.e: Dairi, Karo, Simalungun. The DARwin 5.05 software was used to calculate and descriptive analysis. The results showed that a totally 25 DNA bands were obtained from the amplification of 26 accessions of andaliman using 5 random primers. The size of DNA bands were varied from 400 bp to 2400 bp. The percentage of polymorphic bands were also varied from 75% to 100%. From the 30 accessions there were 26 accessions enabled analyze by the software. The cluster analysis of the 26 accessions of the North Sumatera andaliman plants showed the highly genetic diversity and showed the closely genetic diversity with 3 main cluster and 6 subcluster. Several accessions were grouped based on the population and the others were dispersed. Keyword : Andaliman , genetic diversity, RAPD